Association between Cardiac Outcomes and Indoxyl Sulfate Levels in Hemodialysis Patients: A Cross-sectional Study - Zhuo Li; Guibao Ke; Li Song; Junlin Huang; Yamei Zhang; Jie Xiao; Shuangxin Liu; Xinling Liang (Karger Publishers, 2021)
Objective Indoxyl sulfate (IS) is a protein-bound uremic toxin that is associated with cardiovascular events and mortality in hemodialysis (HD) patients. However, the factors affecting the levels of IS are currently unclear. This study aimed to investigate the factors influencing serum IS concentrations in HD patients. Methods We included 100 HD patients from Guangdong Provincial People's Hospital. Baseline characteristics, including sex, age, clinical features, duration of HD, echocardiography findings, electrocardiogram results, and biochemical indicators, were collected and analyzed in relation to serum total-form IS levels. Results Among all 100 patients, serum IS levels were significantly higher in patients aged ≥ 60 years, males, and patients with mitral regurgitation and inadequate dialysis. Among patients aged < 60 years, IS levels were significantly higher among patients with mitral regurgitation compared with those without. Furthermore, multiple linear regression analysis identified sex, age, ventricular septal thickness, and mitral regurgitation as factors independently associated with serum IS (STDβ = −0.475, 0.162, −0.153, 0.142, and 0.136, respectively; all P < 0.05) adjusted for body mass index, smoking, and fasting plasma glucose. Conclusions Male sex, age ≥ 60 years, ventricular septal thickness, and mitral regurgitation are factors associated with high total serum IS concentrations in Chinese HD patients. Elevated IS levels may play a role in the process of mitral regurgitation in HD patients < 60 years old.